The Importance of Halal Certified Products in Samarinda City: in the light of Maqasid Al-Syari'ah - Hasan, Maisyarah Rahmi (Borneo International Journal of Islamic Studies, 2019)
Halal certification is a guarantee of safety for Muslims to be able to consume a product as evidenced by the inclusion of the halal logo on the product packaging. To realize the "halal awareness" program in Indonesia, public awareness of halal-certified products is very influential in the success of the program's obligations. While in the field there are still many Muslim consumers who do not understand, and still do not prioritize halal certification in every product purchase. Further research is needed related to study the importance of halal certified products in Samarinda City, beacuse there are still many products do not have halal certificate yet. This research is a field research, a type of empirical normative research with a sociological juridical approach by studying and analyzing data obtained in the field with the study of Maqasid Al-Syariah. This research will examine and analyze the importance of halal certification on products circulating in the Samarinda City market, in the light of Maqasid al-Shari'ah.The results of this study indicate that halal certification is very important to be applied in Samarinda City. Meanwhile, if seen from the perspective of maqasid al-shari'ah with the existence of halal certification can realize mashlahah, namely goodness in the lives of Muslim consumers. Because with guaranteed food consumed, maqasid al-shari'ah al-dharuriyah al-khamsah, namely guarding religion, guarding souls, guarding intellect, guarding offspring, and protecting property will be fulfilled. The importance level of halal certification if viewed from the perspective of maqasid al-shari'ah, it can be concluded that halal certification in Samarinda is at the level of hajjiyah, which is needed, which without halal certification does not cause inaccuracies, but can be potentially difficult if there is no halal certification in Samarinda City. Therefore, the need for halal certification in Samarinda City is important because of the needs of Muslim consumers towards it.